The Effect of Perceived Healthiness and Perceived Tastiness on The Intention to Consume Products with High Protein Claims - Bernadette Victoria; Whisnu Trie Seno Ajie; Audria Ineswari Mulya Marhadi (Journal La Medihealtico, 2025)
The growing demand for functional foods has increased consumer interest in products labeled as high in protein. However, determinants of consumers’ intention to consume such products remain inconsistent across studies. This research aimed to examine the effects of nutrition knowledge, health motivation, price, brand, perceived healthiness, perceived tastiness, and online review on consumers’ intention to consume high protein products, both partially and simultaneously. A quantitative analytical survey was conducted among 58 respondents of productive age using a structured questionnaire. Data were analyzed using multiple linear regression. The results showed that, partially, only perceived healthiness and perceived tastiness had a significant effect on intention to consume high protein products (p < 0.05). In contrast, nutrition knowledge, health motivation, price, brand, and online review did not show significant partial effects. Nevertheless, simultaneous testing indicated that all variables collectively had a significant effect on consumption intention (p < 0.05), with a coefficient of determination of 30.7%. These findings highlight that consumers’ intention to consume high protein products is primarily driven by perceptual factors rather than general cognitive or marketing related factors. Therefore, product development and nutrition promotion strategies should integrate credible health claims with positive sensory experiences to encourage sustainable consumption intentions.